Sales Strategy by Determining Tenant Position at Sriwijaya State Polytechnic Through Association Rules Analysis - Indra Griha Tofik Isa (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: The purpose of this research is to optimize the usefulness of sales transaction reports in Sriwijaya State Polytechnic (Polsri) foodcourt and extract sales transaction report data to become the knowledge that can be used in sales strategies that is recommendations for tenant positions in accordance with customer behavior by using association rules analysis. Design/methodology/approach: The approach using Knowledge Discovery in Database through stages (1) Data Selection; (2) Data Classification; (3) Raw Itemset Table; (4) Data Mining Process using Association Rules Analysis; (5) Analysis Result Interpretation; (6) Marketing Strategy Recommendation. Findings: The results of the study are recommendations for tenant positions in accordance with customer behavior tendencies Research limitations/implications: Polsri foodcourt sales transaction report used in the period 01 May 2019 – 31 July 2019, with a total of 153,401 data records, data analysis using Association Rules Analysis with A Priori Algorithm, tools used are Microsoft Excel and WeKa 3.6.10 Practical implications: The recommended tenant position can be used as a sales strategy that makes it easier for customers to choose the product to be purchased and increase sales rate Originality/value: The paper is original Paper type: Research paper